Economic valuation of river systems - Hitzhusen, Fredrick J.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar Pub., 2007)
The book applies benefit-cost analysis and a wide array of non-market and distribution economic valuation methods in ecologic context to determine the pay-off and distribution impacts of various infrastructure and water quality improvements to eight river systems in the Great Lakes region of the US. The generally positive results have important implications for public policy and future research.
1. The role of biology and ecological engineering in watershed and river restoration -- 2. Codification, case studies, and methods for economic analysis of river systems -- 3. Estimating willingness to pay for additional protection of Ohio surface waters : contingent valuation of water quality -- 4. The economics of high-head dam removal in an ecological context : a case study of the Ballville Dam, Fremont, Ohio -- 5. The economics of low-head dam removal : a case study on the Salmon River in Fort Covington, New York -- 6. Economic analysis of infrastructure and water quality improvements in the Muskingum River Corridor -- 7. Economic analysis of water quality and recreational benefits of the Hocking River Valley -- 8. Effects of pesticide use and farming practices on water treatment costs in Maumee River Basin communities -- 9. Economic efficiency and distribution evaluation of dredging of toxic sediments and selected dam removal in the Mahoning River -- 10. An economic analysis of Lower Great Miami River segment improvements -- 11. The Cuyahoga River Valley initiative : framing, codification, and preliminary economic analysis in an urban river corridor -- 12. Overview, key findings, and approaches including benefit transfer for generalization of research results.
Includes bibliographical references and index.
Keywords: Stream restoration -- Economic aspects -- Great Lakes Region (North America) -- Case studies; Watershed management -- Economic aspects -- Great Lakes Region (North America) -- Case studies; Rivers -- Economic aspects -- Great Lakes Region (North America) -- Case studies; Sustainable development -- Great Lakes Region (North America) -- Case studies; Contingent valuation -- Great Lakes Region (North America) -- Case studies; Electronic books